2021
DOI: 10.1186/s12610-021-00138-4
|View full text |Cite
|
Sign up to set email alerts
|

Will whole-genome sequencing become the first-line genetic analysis for male infertility in the near future?

Abstract: Whereas the initially strategy for the genetic analysis of male infertility was based on a candidate gene approach, the development of next-generation sequencing technologies (such as whole-exome sequencing (WES)) provides an opportunity to analyze many genes in a single procedure. In order to recommend WES or whole-genome sequencing (WGS) after genetic counselling, an objective evaluation of the current genetic screening strategy for male infertility is required, even if, at present, we have to take into cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
(29 reference statements)
0
3
0
1
Order By: Relevance
“…The exome, which represents 1% of the human genome, consists of 180,000 exons [ 65 ]. Currently, complex whole exome sequencing represents the diagnostic tool of choice, but it is believed that whole exome sequencing (WES) will be replaced by whole genome sequencing (WGS), which has a lower cost and incorporates practical software facilitating the interpretation of results [ 66 ]. Practically, this has helped in the understanding of several male infertility states; for instance, several genes have been identified in the context of non-obstructive azoospermia (NOA), including FANCA, PLK4, WKN3, MEI1, ADAD2, and TEX11 [ 66 67 ].…”
Section: Male Infertility Diagnosticsmentioning
confidence: 99%
“…The exome, which represents 1% of the human genome, consists of 180,000 exons [ 65 ]. Currently, complex whole exome sequencing represents the diagnostic tool of choice, but it is believed that whole exome sequencing (WES) will be replaced by whole genome sequencing (WGS), which has a lower cost and incorporates practical software facilitating the interpretation of results [ 66 ]. Practically, this has helped in the understanding of several male infertility states; for instance, several genes have been identified in the context of non-obstructive azoospermia (NOA), including FANCA, PLK4, WKN3, MEI1, ADAD2, and TEX11 [ 66 67 ].…”
Section: Male Infertility Diagnosticsmentioning
confidence: 99%
“…На сьогодні проблема безпліддя постає особливо гостро та стосується рівною мірою і жінок, і чоловіків [4,5]. Тому важливо поєднувати медичні, технологічні, правові та організаційно-адміністративні знання (тобто застосовувати комплементарну взаємодію методологічного інструментарію) для комплексного розкриття проблеми репродуктивної діяльності людини, що проявляється в реальних правовідносинах.…”
Section: вступunclassified
“…However, one of the main challenges in the infertility genetics research is the correct interpretation of these reported genetic variations because most of them are being considered as variants of unknown significance (VUS) or benign variants without any clinical significance. Therefore, the development of appropriate tools alongside the expertise of experienced specialists are crucial for the clinical practice [13]. The failure to include monogenic disorders in the diagnostic follow-up despite the growing opportunities of NGS can possibly decrease a quality of the infertility treatment.…”
Section: Introductionmentioning
confidence: 99%